The Effectiveness of Brisk Walking Exercise on Blood Pressure among Elderly Patients with Hypertension: A One-Group Pretest–Posttest Study - Supriyanto Supriyanto; Sherly Aldeiyana Hasan; Hepta Nur Anugrahini; Endang Soelistyowati (International Journal of Advanced Health Science and Technology, 2026)
Hypertension remains one of the leading causes of cardiovascular morbidity and mortality among older adults worldwide. Despite the widespread use of antihypertensive medication, blood pressure often remains poorly controlled because pharmacological treatment alone is insufficient without complementary lifestyle modifications. Brisk walking exercise has been recommended as a practical non-pharmacological intervention; however, evidence regarding its effectiveness among elderly individuals residing in nursing homes, particularly in Indonesia, remains limited. This study aimed to evaluate the effectiveness of brisk walking exercise in reducing systolic and diastolic blood pressure among older adults with hypertension living in a nursing home. A quasi-experimental study employing a one-group pretest–posttest design was conducted involving 18 older adults with hypertension selected through purposive sampling. Participants performed brisk walking exercise for 20 minutes, six sessions over two weeks, at an intensity adjusted to their physical capacity. Blood pressure was measured before and after the intervention using a calibrated digital sphygmomanometer. Data were analyzed using the Wilcoxon Signed-Rank Test for systolic blood pressure and the paired-sample *t*-test for diastolic blood pressure. The mean systolic blood pressure decreased from **151.00 ± 9.49 mmHg** before the intervention to **125.89 ± 11.68 mmHg** afterward, while the mean diastolic blood pressure decreased from **94.00 ± 7.67 mmHg** to **77.67 ± 5.08 mmHg**. Statistical analysis demonstrated significant reductions in both systolic and diastolic blood pressure (both *p* < 0.001), with large effect sizes, indicating a substantial impact of the intervention. These findings suggest that brisk walking exercise is an effective, safe, and feasible complementary non-pharmacological strategy for improving blood pressure control among elderly individuals with hypertension. Incorporating regular brisk walking into routine nursing care may contribute to better cardiovascular health and reduce the risk of hypertension-related complications in institutionalized older adults.